ANAL SPHINCTER TRANSECTION-REPAIR BY OVERLAP SPHINCTEROPLASTY: Anal Sphincter Transection - Qureshi, Muhammad Azhar (Pakistan Armed Forces Medical Journal, 2007)
INTRODUCTIONAnal sphincter transection is a serious injury whether due to obstetric mismanagement or non-obstetric trauma. Most of these cases result from damage to anal sphincter mechanism in 3rd or 4th degree perineal tears. Non-obstetric causes are the result of transanal impalement injuries, anal intercourse, anal rape, and as a result of fall over projected objects. These injuries may also occur in hyperabduction of thighs in motor vehicle accidents, when a perineal laceration can extend through the anus into the rectum. Repair of anal sphincter was traditionally done with end-to-end repair but now the preferred method of sphincter repair is by overlapping technique [1].